Dinuclear tethered pyridine, diimine complexes12. Issue 35 (30th July 2018) - Dammann, Wiebke; Buban, Tabea; Schiller, Carl; Burger, Peter
Abstract : Synthesis and structures of aryl tethered pyridine, diimine complexes. Abstract : The regioselective borylation of pyridine precursors, followed by Suzuki coupling with dihalogenated linker molecules, provides access to tethered ligands. Complexation with MX2 salts results in the formation of dinuclear metal compounds. Syntheses and crystal structures are reported along with a discussion on the rigidity/flexibility of these new ligand systems.